2022
DOI: 10.3390/nano12050879
|View full text |Cite
|
Sign up to set email alerts
|

Foam Synthesis of Nickel/Nickel (II) Hydroxide Nanoflakes Using Double Templates of Surfactant Liquid Crystal and Hydrogen Bubbles: A High-Performance Catalyst for Methanol Electrooxidation in Alkaline Solution

Abstract: This work demonstrates the chemical synthesis of two-dimensional nanoflakes of mesoporous nickel/nickel (II) hydroxide (Ni/Ni(OH)2-NFs) using double templates of surfactant self-assembled thin-film and foam of hydrogen bubbles produced by sodium borohydride reducing agent. Physicochemical characterizations show the formation of amorphous mesoporous 2D nanoflakes with a Ni/Ni(OH)2 structure and a high specific surface area (165 m2/g). Electrochemical studies show that the electrocatalytic activity of Ni/Ni(OH)2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…It is proposed that methanol is oxidized on NiO NPs/TiO 2 NTs‐N 2 electrode through the reaction with NiO(OH) to form Ni(OH) 2 ; that is, NiO(OH) acts as electron transfer mediator for the oxidation process. [ 73 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is proposed that methanol is oxidized on NiO NPs/TiO 2 NTs‐N 2 electrode through the reaction with NiO(OH) to form Ni(OH) 2 ; that is, NiO(OH) acts as electron transfer mediator for the oxidation process. [ 73 ]…”
Section: Resultsmentioning
confidence: 99%
“…It is proposed that methanol is on NiO NPs/TiO 2 NTs-N 2 electrode through the reaction with NiO(OH) to form Ni(OH) 2 ; that is, NiO(OH) acts as electron transfer mediator for the oxidation process. [73] The catalytic activity of NiO NPs/TiO 2 NTs-N 2 for methanol oxidation was assessed by CV. Figure 11 shows the cyclic voltammograms of NiO NPs/TiO 2 NTs-N 2 in 2-M KOH and 0.5-M CH 3 OH.…”
Section: Methanol Oxidation Of Nickel Oxide Nanoparticles Upheld On T...mentioning
confidence: 99%
“…The CPE is corresponding to the double layer capacitance and the charge transfer resistance, C 2 and R 3 are the electrical elements related to the adsorption of reaction intermediates for methanol oxidation. 77,78 In a study, it was observed that the R ads value decreased with the decrease in the R ct value during methanol oxidation. 79 The sum of R ct and R ads is defined as the total resistance involved in the Faradaic process (R far ) and lower resistances indicated more efficient in methanol oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…The suitable circuit was shown in the inset of Figure 14A. The CPE is corresponding to the double layer capacitance and the charge transfer resistance, C 2 and R 3 are the electrical elements related to the adsorption of reaction intermediates for methanol oxidation 77,78 . In a study, it was observed that the R ads value decreased with the decrease in the R ct value during methanol oxidation 79 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the soft-template approach as the chemical method has been widely exploited because of its one-step route that produces high-surface-area mesoporous nanostructured compounds [ 52 , 53 , 54 ]. Using this approach, our research group reported a foam-surfactant dual template (FSDT) approach to produce mesoporous Ni/Ni(OH) 2 2D nanoarchitecture (nanoflakes) via chemical deposition from a hexagonal lyotropic surfactant template using a sodium borohydride reducing agent [ 55 ]. The Ni/Ni(OH) 2 nanoflake catalyst has shown substantial enhancement of the electrochemical nature of methanol and urea oxidation and glucose sensing reactions [ 51 ].…”
Section: Introductionmentioning
confidence: 99%